Nonsurgical management of ulnar collateral ligament injuries is tentatively successful in overhead athletes: a critical appraisal of case series - Oakes, N.; McKeon, J. M. M. (International Journal of Athletic Therapy & Training, 2020)
Since its inception, surgical management of the ulnar collateral ligament (UCL) is fairly standard; however, the invasive, costly, and time-intensive nature of UCL surgery may be restrictive to some athletes. Electronic databases were searched starting from the year 2013 to September 2018. Extracted data included frequencies of (a) return to play (RTP); (b) return to same level of play (RTSP); (c) athlete`s position; (d) complete reconstitution of the UCL; and (e) the location of ligament rupture (proximal or distal). Proportions of success/failure for selected outcomes were calculated. Additionally, an odds ratio (OR) (95% confidence interval [CI]) determined the association between tear location (proximal vs. distal) and nonsurgical success. A total of 169 athletes underwent nonsurgical management of UCL injury in the seven included studies. Sports included baseball, gymnastics, softball, hockey, volleyball, and tennis. Overall, 83% (n = 140) were able to RTP and 72% (n = 121) were able to RTSP. Those with proximal UCL tears had a RTSP rate of 82% (n = 56) compared to 42% (n = 13) of those with a distal tear. Proximal tears were associated with higher rates of successful outcomes in RTP and RTSP (OR = 6.5 [2.5,16.7], p < .001). In baseball, 76% (n = 38) of pitchers were able to RTSP compared to 90% (n = 9) of position players. When visualized using MRI, 96% (n = 22) of athletes had full UCL reconstitution following nonsurgical management. Based on the pooled outcomes of included studies, nonsurgical management of a UCL injury was reasonably successful for RTP and RTSP rates in professional athletes, with a better chance of success for proximal tears compared to distal and incomplete tears compared to complete. The exploratory nature of utilizing nonsurgical management for UCL sprains in athletes, by way of the case series, appears to be fairly well established, but an upgrade in study design is warranted.